Glucose levels by age and body mass index in urban and rural areas of Venezuela - Avila, Ayari (2020)
Introduction: Urban and rural areas present differences in relation to lifestyle, which influences the presence of metabolic endocrine diseases and hyperglycemia. Objective: To compare blood glucose levels by age and Body Mass Indices in urban and rural areas. Materials and methods: A descriptive, cross-sectional and correlational study was carried out, from January to July of the year 2019, in urban and rural areas. A sample of 124 individuals from urban areas and 95 from rural areas were studied by intentional sampling; hyperglycemia screening was performed by capillary sample using a glucometer, in turn the following data were collected: weight, height, age and sex. The data were processed in the SPSS program (20), analyzed using frequencies, descriptive statistics, and inferential statistics at 95% confidence. Results: Higher glycemic values ​​were observed in men (106.0 ± 29.2 mg / dL), without finding significant differences by sex; 63% had an age greater than or equal to 50 years; constituting the age group where higher blood glucose levels were observed (106.7 ± 30.3 mg /dL), showing differences between both groups. No glycemic differences were found according to the Body Mass Index. In urban areas, 26% of patients presented hyperglycemia (> = 101 mg / dL) vs 11.9% in rural areas. When comparing blood glucose levels according to the origin, they were higher in the urban area (106.9 ± 30.8 mg / dl). Conclusion: Blood glucose values ​​were higher in the urban area, and the glycemia levels increased with older age.